2015
DOI: 10.1590/s1984-82502015000300010
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of an emulsion containing lycopene for combating acceleration of skin aging

Abstract: Lycopene, a carotenoid and potent antioxidant is found in large quantities in tomatoes. Lycopene combats diseases, such as cardiovascular disease and different types of cancer, including prostate cancer. However, its topical use in emulsion form for the combat of skin aging is under-explored. The aim of the present study was to develop an emulsion containing lycopene extracted from salad tomatoes and evaluate its cytotoxicity, stability, rheological behavior, antioxidant activity and phytocosmetic permeation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Previous studies have already demonstrated the importance of the rheology of the pharmaceutical product, stating that the determination of the rheological behavior of the formulation aids in the evaluation of the physicochemical nature of the vehicle in such a way that makes it possible to detect early signs of physical instability allowing control quality of constituents, testing formulations and final products (Cefali, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have already demonstrated the importance of the rheology of the pharmaceutical product, stating that the determination of the rheological behavior of the formulation aids in the evaluation of the physicochemical nature of the vehicle in such a way that makes it possible to detect early signs of physical instability allowing control quality of constituents, testing formulations and final products (Cefali, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Emulsion is a system consisting of two immiscible liquids, containing one aqueous or hydrophilic part and another oily or lipophilic, where one of the parts is dispersed in another as droplets, becoming homogeneous by the addition of surface-active substances which emulsify the system (Cefali, 2009).…”
Section: Development Of Phytocosmetics In Brazilmentioning
confidence: 99%
“…This change may have occurred due to the evaporation of water when the phytocosmetic and the control were in the heater. 16,10 For the parameter pH stability was observed from the 10th day of analysis, as shown on Figure 1. The control behaved similarly to the phytocosmetic, which demonstrates that adding glycinin did not alter the properties of the components of the emulsion.…”
Section: Accelerated Stability Testmentioning
confidence: 96%
“…The parameters were analyzed involved possible alterations in aspect, color, smell, pH value and separation of phases. 16 Regarding the parameter aspect, the product must remain intact during all the days of analysis, maintaining the initial appearance, except in high temperatures, freezer or freezing and thawing cycles, when small alterations are acceptable. Regarding the parameters color and smell, they must be stable during the 15 days of testing and small alterations are acceptable only in high temperatures.…”
Section: Accelerated Stability Testing (Ast)mentioning
confidence: 99%
“…In the formulation containing GB extract, the soft extract was solubilised in 10% of the water (discounted from the total water content of the formulation). Right after preparation and cooling, the extract solution was mixed with vigorous agitation (Cefali et al, 2015).…”
Section: Design Of the Cosmetic Formulationmentioning
confidence: 99%